Learning Outcomes Using The Problem-Solving Learning Model Based Learning On The Material Of Volleyball Overhead Passing Class VII. 5 State SMP Negeri 33 Palembang (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The learning outcomes of physical education, sports, and health (PJOK) students are still relatively low due to the lecture method and one-way learning or teacher-centred learning used in learning, making students feel bored and sleepy. This study aims to improve the learning outcomes of physical education, sports, and health (PJOK) students of class VII.5 SMP Negeri 33 Palembang on the material of volleyball overhead passing through the Problem-Based Learning (PBL) learning model with the Teaching at the Right Level (TaRL) approach. This study uses the Classroom Action Research (CAR) method, which is carried out in 2 cycles, and each cycle consists of 2 meetings. The subjects in this study were 31 students of class VII 5 SMP Negeri 33 Palembang, with 14 male students and 17 female students. The data collection technique in this study used a written test technique. The data analysis technique used is quantitative descriptive analysis. The results of the analysis showed that student learning outcomes increased from 54.83% in cycle I to 87.09% in cycle II. Based on the research results, it can be concluded that the Problem Based Learning (PBL) learning model with the Teaching at the Right Level (TaRL) approach can improve the learning outcomes of physical education, sports, and health (PJOK) of class VII.5 students of SMP Negeri 33 Palembang on the volleyball overhead passing material.